Genetic identification and expression optimization of a novel protease HapR from Bacillus velezensis - Han, Zhenying; Ye, Changwen; Dong, Xinyu; Chen, Chenchen; Zou, Dian; Huang, Kuo; Wei, Xuetuan (Frontiers in Bioengineering and Biotechnology, 2024)
Due to the broad application and substantial market demand for proteases, it was vital to explore the novel and efficient protease resources. The aim of this study was to identify the novel protease for tobacco protein degradation and optimize the expression levels. Firstly, the tobacco protein was used as the sole nitrogen resource for isolation of protease-producing strains, and a strain with high protease production ability was obtained, identified as Bacillus velezensis WH-7. Then, the whole genome sequencing was conducted on the strain B. velezensis WH-7, and 7 proteases genes were mined by gene annotation analysis. By further heterologous expression of the 7 protease genes, the key protease HapR was identified with the highest protease activity (144.19 U/mL). Moreover, the catalysis mechanism of HapR was explained by amino acid sequence analysis. The expression levels of protease HapR were further improved through optimization of promoter, signal peptide and host strain, and the maximum protease activity reaced 384.27 U/mL in WX-02/pHY-P43-SPyfkD-hapR, increased by 167% than that of initial recombinant strain HZ/pHY-P43-SPhapR-hapR. This study identified a novel protease HapR and the expression level was significantly improved, which provided an important enzyme resource for the development of enzyme preparations in tobacco protein degradation.